Ragna Crimson. 6 - Kobayashi, Daiki (Manga artist) (Square Enix Manga, 2022)
"Together with the Argentum Corps, Ragna and Crimson face off against a swarm of dragons led by Olto Zora, the Mad Maestro Dragon, and Taratectra, the Explosive Dragon. It's Ragna's one-hit-kill sword versus Taratectra's devastating blows, with the outcome of the battle hanging by a thread. Then the Mad Maestro springs a surprise attack against the Argentum Corps base, placing the entire force in peril!"--Back cover.